Changes in the epidemiological patterns of respiratory syncytial virus and human metapneumovirus infection among pediatric patients and their correlation with severe cases: a long-term retrospective study - Kuang, Lu; Xu, Tiantian; Wang, Changbing; Xie, Jiahui; Zhang, Yingying; Guo, Min; Liang, Zhuofu; Zhu, Bing (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectivesWe aim to investigate the prevalence of respiratory syncytial virus (RSV) and human metapneumovirus (hMPV) among pediatric patients with acute respiratory tract illness (ARTI) in southern China both pre- and post-COVID-19 pandemic, as well as identify associated risk factors for severe infections.MethodsThe study conducted a real-time PCR analysis on hospitalized children with ARTI from 2012 to 2023, specifically targeting RSV, hMPV, and other respiratory pathogens. Additionally, demographic data was collected during this analysis.ResultsThe prevalence of RSV occurs triennially, and likewise, the temporal pattern of hMPV outbreaks mirrors that of RSV. The peak infection rates of RSV and hMPV occurred during and following the implementation of COVID-19 epidemic prevention and control measures. The incidence of RSV infection exhibited bimodal peaks in 2022, while hMPV demonstrated seasonal peaks during the spring, fall, and winter periods post-COVID-19 pandemic. After the COVID-19 outbreak, there has been an upward trend in the proportion of female patients and patients aged one year and older presenting with ARTI, RSV infections, and hMPV infections. Infant (OR = 4.767, 95%CI: [3.888–5.846], p < 0.0001), presence of co-infection (OR = 0.540, 95%CI: [0.404–0.722], p < 0.0001), and existence of comorbidities (OR = 1.582, 95%CI: [1.285–1.949], p < 0.0001) was the risk ratio for the severity of RSV infection. Children infected with hMPV under the age of 1 year (OR = 0.322, 95%CI: [0.180 – 0.575], p < 0.0001), as well as those with comorbidities (OR = 8.809, 95%CI: [4.493 – 17.272], p < 0.0001), have a higher risk of developing severe illness.ConclusionThe changing epidemiological patterns have the potential to lead to widespread severe outbreaks among children, particularly those with underlying medical conditions who may experience more severe symptoms. Conducting surveillance for pneumoviridae viruses in children is an imperative measure to establish a robust foundation for future epidemic prevention and treatment strategies.